PERBAIKAN TANAH PADA TANAH GRANULAR DENGAN VIBROCOMPACTION - Dyah Pratiwi Kusumastuti (FORUM MEKANIKA, 2016)
Land requirements in big cities like Jakarta continues to increase with the growth in infrastructure development. Often the development and utilization of such land should be carried out on land that does not in accordance with the requirements. For example construction on the ground that is less stable during vibration or earthquake as granular soils. Compaction method is generally preferred in granular soil improvement because the method is suitable for use in soil layers not berkohesi that is not solid enough. Land improvements made to the land that has a fairly low technical characteristics become viable material used as a construction material. Benefits of using the technique of vibro compaction, among other things increase the weight of the volume of soil, reducing the decline foundation and reduce the impact of liquefaction.